Ideologi Media dan Pembingkaian Berita Masjid Al Jabbar di Portal Jabarprov dan Jabar News - Herlina, Dewi; Firmonasari, Aprillia (Humanis; Vol 27 No 3 (2023), 2023)
This research aims to construct media bias in the discourse of news articles written by journalists. This research aims to analyze the framing structure and explore ideological differences between the two media regarding the news of the inauguration ceremony of Al Jabbar Mosque. This study uses a qualitative descriptive approach. The data consists of written utterances in news articles taken from the Jabarprov and Jabar News Portal. The data analysis method refers to Pan and Kosicki's framing theory. Based on the research findings, there was a tendency of media bias observed. in their framing influenced by the ideological differences between the two media. In this case, Jabar Prov Portal, which has a pro-government ideology, tends to highlight the beauty of the construction of Al Jabbar Mosque. Meanwhile, Jabar News, which has a pro-people ideology, gives prominence to the issue of the budget for Al Jabbar Mosque. This has sparked controversy among the people of West Java regarding the coverage of Al Jabbar Mosque in the two local media.